Stages in Human Resource Development in Da'wah Institutions - Muhammad Ronaydi; Cecep Castrawijaya (International Journal of Social Service and Research, 2023)
This study aims to determine the stages carried out in the development of human resources in da'wah institutions. This study used qualitative descriptive method. Based on the results of writing that has been done about the stages of human resource development in da'wah institutions. It was found that the stages of human resource development in da'wah institutions can be carried out in several stages, namely, First, Providing Training / Education, then Second, Rotating positions so that existing human resources can develop by gaining new experience in work, Third, Leaders do good delegation, Fourth, there is a promotion of course, with this the existence of HR will always be enthusiastic to provide innovations and always try to improve its performance in work. Fifth, Transfer employees, Sixth, Good counseling between superiors and subordinates or between seniors and juniors within the institution or also closer between the head of the field and its members, especially counseling in work so that performance is always stable and increases. Then the last or the Seventh, which is to hold a conference.